STABILITY OF SYSTEMS WITH RETARDATION IN THE CASE OF SMALL INTEGRAL PERTURBATIONS - Shahinyan, S. G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2001)
The paper considers the problem of stability of nonlinear differential equations systems with retardation when small integral perturbations effect the system in finite interval of time. Sufficient conditions are obtained, under which such systems are stable according to the acting force.